A DEVELOPİNG A BUSİNESS WİTH OUTSOURCİNG USİNG THE İNTERNET - Perisich, Jasmina; Ajrula, Jusuf (International Scientific Journal Vision, 2019)
Internet changed the wold and the whole business from period when digital products started to be ordered and payed online then which also started to get delivered to the customers by internet, instead of ordering physical products through internet and delivering them to the customers prhysically. With that businesses realised the power of internet and lots of newmethods of doing business over the internet has emerged. One of those new methods that has emerged is arranging human resorses over internet, that is called outsourcing. In this paper outsourcing through internet will be covered in depth, by clearly stating the difference among outsourcing people online and on tradional ways and defining the strenghts and weaknesses of online versus tradional outsourcing. Then an empyrical analysis of outsourcing will be made of one international and one Macedonian SMEs, and a diagnose of situation and opportunities of developing a business with outsourcing using the internet will be shown. By which, businesses can differ and measure the power of hiring outsourced people online and by tradional ways.